Challenges and trajectories of fiscal policy and PFM reform in CEE/CIS - Branka Andjelkovic; Alexandr Chubrik; Marek Dabrowski; Roman Mogilevskiy; Irina Sinitsina; Przemyslaw Wozniak (Center for Social and Economic Research (CASE), 2010)
The purpose of this study is to provide an overview of fiscal policies and PFM reforms in 7 countries in the Western Balkans and 12 countries in the CIS, including major macroeconomic and poverty trends, fiscal policy, the size and role of the public sector, public expenditure management and its linkage to policy development, the organization of budget processes on the central and local levels, the role of various actors and tools in PFM, including civil society and the international donor community. The period of 2003-2007 was characterized by an extraordinary high rate of economic growth, both worldwide and in the CEE/CIS region. This created macroeconomic room for meeting numerous development challenges: reducing poverty and inequality, improving the quality and coverage of public services, upgrading infrastructure, and advancing various reforms, including those related to PFM. However, the economic situation deteriorated dramatically in 2008 as a result of the global financial crisis, with deep recession hitting most of the countries in 2009 and bleak perspectives for subsequent years. It remains to be seen whether the crisis situation will force governments to speed up necessary reforms. In the PFM area major tasks concern lengthening fiscal planning horizon and gradual movement toward performance oriented budgeting (the measure which can allow better expenditure targeting and decrease volatility in expenditure allocation), increasing budget transparency and creating real room for civil society involvement into a budget process. However, the reforms must also involve a broadly defined governance sphere, i.e. improving transparency and accountability of government, modernization of civil service, decentralization, including building a genuine system of local and regional self-government, and other similar measures to improve quality of public services and social policy interventions.
Keywords: H51; H52; H53; H61; H62; H63; H77; P36; 330; public finance management; fiscal policy; Central and Eastern Europe; Western Balkans; Commonwealth of Independent States; social policies; social services; children and families; Finanzpolitik; Öffentliche Finanzen; Öffentliche Ausgaben; Öffentlicher Haushalt; Osteuropa; GUS-Staaten